Unravelling the Role of Epigenetic Modifications in Development and Reproduction of Angiosperms: A Critical Appraisal - Kumari, Priyanka; Khan, Sajid; Wani, Ishfaq Ahmad; Gupta, Renu; Verma, Susheel; Alam, Pravej; Alaklabi, Abdullah (Frontiers in Genetics, 2022)
Epigenetics are the heritable changes in gene expression patterns which arise without altering DNA sequence. Epigenetic mechanisms include DNA methylation, histone modification and RNA-mediated mechanisms which stably alter pattern of gene expression primarily at transcriptional level. Interaction of plants with their environment involves modifications in their gene expression order. Epigenetic alterations affect the developmental changes from vegetative to reproductive stage which are highly regulated by a composite network of genes. Genes control flowering time in plants by undergoing genetic and epigenetic reprogramming leading to fruit and seed set. This also ensures flowering under stress conditions. Environmental and hormonal signals work in integrated manner to promote flowering through epigenetic regulation. Phytohormones including gibberellins, jasmonic acid, abscisic acid, auxins facilitate compaction of chromatin and subsequent transcriptional suppression intervened by DNA methylation. This suggests the role of epigenetic regulation in flowering through hormone action. Here we review epigenetic regulations involving changes of DNA methylation, histone modifications, miRNAs, plant hormones signaling pathways during plant developmental processes and association of epigenetic modifications with flower initiation and growth and stress tolerance. DNA methylation controls genome activity of plants through transcriptional silencing of transposable elements thereby contributing towards genome stability.